THE SOCIAL WORK STUDIES AT VILNIUS UNIVERSITY: THE REFLECTION OF FIFTEEN YEARS - Bagdonas, Albinas; Lazutka, Romas (Socialinė teorija, empirija, politika ir praktika, 2007)
The goal of the paper is to present the development of social work studies in Vilnius University. According to authors, there are nine groups of variables for study program. There has to be a theoretical basis for a certain study program. There is no unified theoretical framework in social work and that is a problem for social work. The second condition is an existence of study program. The peculiarities of labour market for social workers imposed two different ways to organise social work study. The first one was a study program for the re-skilling workers of social care institutions. The other, was an ordinary study program. There cannot be a study program without academic stuff. The members of social work department were academics from related disciplines (psychology, education, economics and so on) in the beginning. Latter the grown ups academics joined the department. Other agencies organise social work study programs, also. In some cases, it is competition in other – cooperation. The social work study program is organised in different ways and there is a discussion about which way has to choose Lithuania. The sixth dimension is the demand for the study program. The demand is reflected by the employment of graduates. The study process primary depends on academic staff, but physical and technological conditions are also important. The university is connected with other agents in the field – social work schools, public sector organisations, civil society and research agencies. If the goal of organisation is to remain in the field, it has to react to feedback from students, employees and social partners.
Keywords: Study organisation; Social work; Vilnius University